Comparação de dois métodos de detecção da instabilidade de tensão baseados em medição fasorial e equivalente de Thévenin - Ferreira, Alan de Paula Faria (2017)
Evaluation and comparison of two methods for voltage stability assessment in power systems. They are the Topological Monitoring Method Duong (MBTDUONG) and the Adaptive Identification Method Corsi-Taranto (MBM-CT). Both algorithms have a characteristic of using phasor measurements from PMUs to make their estimates, which are based on the determination of the Thevenin equivalents of the load buses to be analyzed, comparing the values obtained with the impedance values of these ones. Thus, using the Maximum Power Transfer Theorem, a proximity of the voltage instability will be associated with the moment of the impedance matching. Their performance is analyzed for different load modeling, actuation of over-excitation limiters (OELs), actuation of on load tap changers (OLTCs), systemic contingency and limitation of active generation (turbine limits). The simulations were performed in two systems: 3-Bus System and WSCC 9-Bus System. The simulation is performed in the time domain, using the power system analysis toolbox PSAT for Matlab.Também disponível on-line.